RANCANG BANGUN SISTEM PENGUNCI LOKER OTOMATIS DENGAN KENDALI AKSES MENGGUNAKAN RFID DAN SIM 800L - I Komang (Universitas Teknokrat Indonesia, 2020)
A storage box / locker is a facility used by people to store goods. Storage boxes are often found in buildings both in offices and in schools and other public places. Usually the existing storage box in a building still uses conventional keys. If using a conventional key security of goods in the box is still not guaranteed, but if you use an automatic item storage security system using RFID and Sim 800L, then the goods stored in the box will be guaranteed security and more efficient in its use.